(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sushadi DS, Phadmacanty NLPR, Wahyudin M, Wirdateti 2021. Short Communication: Infanticide of Javan slow loris (Nycticebus javanicus) in captivity. Biodiversitas 22: 1606-1611. Over the past decade, the population of Javan slow loris (Nycticebus javanicus) in the wild has continued to decline. Various conservation efforts by the government and NGOs have been carried out, but still have not yielded significant results. Many studies have highlighted the impact of poaching and forestland conversion as a cause, but the natural behavior of N. javanicus, especially infant care interactions, is poorly studied. We investigated the case of a 5-day-old Javan slow loris baby named Monda, found dead in captivity. Monda was born in captivity and impounded with its mother and an adult male. She was found dead decapitated with a sign of injury on the right arm. Microscopic fecal examination of the other lorises showed hair and bone fragments in the male feces. Based on this finding, it is possible that infanticide also occurs in slow lorises in its natural habitat but may have been underreported.